Taboo language and censorship in the italian dubbing of "Ted 2" (Lingue e culture dei media, 2017)
An increasing use of taboo language on TV has hallmarked the American film industry over the last decades. Ted 2 (2015) is a film rich in taboo and obscene language. By analysing the swearwords uttered in Ted 2, this paper will try to explore whether the Italian version keeps pace with the change and does justice to the film language. At first, the original film taboo language will be examined. To do that, the swearwords will be divided into sexual, scatological and religious offences. The analysis will bring to the fore the fact that sexual swearwords prevail. Then, the Italian version will be considered. The findings will bring to the surface some controversial translation choices. As a matter of fact, although the majority of the swearwords of the Italian version revolves around sex, a great deal of the original swearwords are censored or lessened. Furthermore, a significant discrepancy concerns religious offences, as the Italian version has none. Nevertheless, the audiovisual translation of Ted 2 adheres to the original film language and scene outrageousness more than ever before. New translation patterns in fact emerge, which will hopefully pave the way to acceptable equivalents in film dubbing.